Bioremediation of Aquatic Environment Using Weeds - N. T. Yadu Raju; M. Madhavi; T. Ram Prakash (International Journal of Economic Plants)
Water is a resource that supports life and contamination of water resulting from anthropogenic activities, is a matter of concern worldwide. Water defects and contamination of existing water supplies threaten to be critical environmental issues today for agricultural, domestic and industrial uses. Discharge of municipal sewage and industrial activities deteriorate water quality in urban areas. Synthetic fertilizers, herbicides, insecticides and plant residues released from agricultural activities change the water quality in rural areas. Aquatic plants grow profusely in lakes and waterways all over the world and in recent decades their negative effects have been magnified by man’s intensive use of water bodies. Eradication of the weeds has proved almost impossible and even reasonable control is difficult. Turning these weeds to productive use would be desirable if it would partly offset the costs involved in mechanical removal. Among other uses, there has been considerable interest in using aquatic plants for pollution control. Aquatic macrophyteshave been reported to be very efficient in accumulation of heavy metal ions from the water in which they are growing. Bioremedetion is a waste management technique that involves the use of organisms to remove or neutralize pollutants from a contaminated site. Bioremediation exploits the natural capability ofliving organisms to clean environment. It aids in transformation and degradation of contaminants into non-hazardous or less hazardous substances.